Study the carotid Doppler and computed tomography of head in ischemic stroke patients - Tilchan Pandey; Jeevan Khanal; Shami Pokhrel; Himal Ghimire; Bikash Poudel (Asian Journal of Medical Sciences, 2024)
Background: A stroke is an episode of acute neurological dysfunction from either ischemic infarction or a collection of blood within the brain or ventricular system with resultant focal injury of the central nervous system. The estimated global incidence of stroke is 2–3/1000 person-years, with older patients and patients with carotid artery stenosis or atrial fibrillation having the highest risk. Hence, carotid studies may help with early prevention and management in patients. Aims and Objectives: We aimed to study the prevalence of carotid artery stenosis in acute ischemic stroke and the association of risk factors. Materials and Methods: This was a descriptive study conducted in the department of internal medicine over a period of 6 months. It was carried out in 125 ischemic stroke patients’ inpatient departments. The ischemic stroke was established with history, examination, and computed tomography (CT) with carotid color Doppler study for percentage of stenosis. Results: The 47 (37.6%) stroke patients had carotid stenosis <50% and 78 (62.4%) had >50%; out of them, 32% (40) had (≥50–69%) stenosis, 24% (30) exhibited 70–99%, and 6.4% (8) reported total occlusion. In the CT brain, lacunar infarcts were found in 42 (33.6%), normal and middle cerebral artery infarcts in 27 (21.6%), anterior cerebral artery infarcts in 17 (13.6%), and posterior cerebral artery infarcts in 12 (9.6%). In clinical profiles, 75 (60%) patients presented with right-sided hemiparesis, 50 (40%) with left-sided hemiparesis, 62 (49.6%) with loss of consciousness, 28 (22.4%) with dizziness, and 31 (24.8%) with motor aphasia. Conventional risk factors include hypertension in 68 (54.4%), diabetes in 39 (31.2%), dyslipidemia in 58 (46.4%), heart disease in 65 (52%), and smoking in 51 (40.8%). In the present study, the majority of patients found carotid stenosis >50%, lacunar infarcts were the most common CT findings, and right hemiparesis was common paresis. Hypertension was the most common risk factor among others, and all were significant (P<0.05) for the stroke. Conclusion: There is a high prevalence of carotid stenosis, with >50% in ischemic stroke patients with hypertension being the most common risk factor.